Pemanfaatan Teknologi Rocket Stove sebagai Solusi Pembakaran Sampah yang Efisien dan Ramah Lingkungan - Desca Priyo Anggoro; Puja Mutia Khanza; Evi Handayani; Nandini Putri Nurfajar (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Household waste remains a significant environmental issue, particularly in areas lacking proper waste management systems. Open burning, commonly practiced by communities, produces harmful emissions and negatively impacts air quality and human health. This study aims to design and evaluate a rocket stove-based waste incineration system as an efficient and environmentally friendly alternative. The research method includes design, fabrication, and performance testing based on the Top-Lit UpDraft (TLUD) principle. The results show that the rocket stove reduces combustion time from 45 minutes to 25 minutes and decreases residue from 1.2 kg to 0.3 kg. In addition, smoke emissions are significantly lower compared to open burning. Therefore, rocket stove technology has strong potential as an efficient, low-cost, and environmentally friendly household waste management solution.